2021
DOI: 10.1177/1356336x211047866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sport Education model on adolescents’ motivational, emotional, and well-being dimensions during a school year

Abstract: Research on the impact of the Sport Education model (SEM) in motivational terms is prolific and consistent; however, studies that jointly address the effects of the SEM on adolescents’ motivational, emotional, and well-being dimensions are scarce. This study aimed to examine the effect of a multi-season SEM-based program on self-determined motivation, basic psychological needs, emotional intelligence, satisfaction with life, and the intention to be physically active on physical education (PE) students during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 59 publications
6
13
0
Order By: Relevance
“…The results of this study show a direct and positive relationship for some questions but a negative relationship for others. Thus, focusing on the results that show a direct and positive correlation, we found a relationship between emotional intelligence and motivation, as other studies already showed [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of this study show a direct and positive relationship for some questions but a negative relationship for others. Thus, focusing on the results that show a direct and positive correlation, we found a relationship between emotional intelligence and motivation, as other studies already showed [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 74%
“…The same situation is found for the self-concept of athletes; we found a direct and positive relationship between self-concept and the levels of emotional intelligence [ 10 ]. As with motivation, studies showed that high levels of emotional intelligence have a continuous and existing correlation with self-concept [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are important, drawing attention to the differences that may exist in this case according to gender and EQ and gender and self-determination theory, which coincide with previous research, which, like our work, has highlighted the fact that high levels of emotional intelligence correlate with higher satisfaction of the three basic psychological needs [ 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it has been shown that in the case of motivation, there is a positive correlation with EQ [ 11 , 12 , 13 , 14 ]. However, there is not much agreement on the differences established between sexes in this regard [ 10 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results obtained in this work demonstrate, in our case, that emotional intelligence favors the positive development of aspects such as competence and decision making in athletes. This is along the same lines as other studies that have attempted to determine the relationship between self-determination theory and emotional intelligence, the results of which also corroborate that high levels of emotional intelligence are associated with greater satisfaction of the three basic psychological needs [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 83%